Organizational consulting models and performance improvement : the case of rural schools in Lithuania - Nedzinskaite-Maciuniene, Rasa (Array, 2020)
This study is concerned with a possible organizational consulting model of schools in rural areas with unfavorable social, economic and cultural (SEC) environments. Specifically, the study offers a case study analysis of five rural schools of one Lithuanian municipality. The results yield a conceptual framework for a model of rural school consultation. The proposed model is in line with the theoretical approaches of the dynamic and the ecological theories. The obtained research results offer suggestions and insights for organizational development theory and practice.